PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI RS “X” - Ryan Sarbini; CSP. Wekadigunawan; MF. Arrozi (JURNAL DARMA AGUNG, 2023)
Hospital "X" is a private type C hospital in Sukabumi City that is committed to providing high-quality health services for patients and their families. This study aims to analyze the impact of work motivation and the work environment on employee performance, with job satisfaction acting as an intervening variable. The research used a quantitative approach and survey method with a sample of 197 permanent employees of "X" Hospital. The data analysis employed a path analysis structural equation model. The study found that work motivation and work environment have a significant positive impact on employee performance, with job satisfaction playing a mediating role. Based on the results, the hospital management can evaluate employee performance and provide appropriate rewards, promotions, and continuing education to improve employee work motivation, job satisfaction, and performance.